2014
DOI: 10.1186/1479-7364-8-4
|View full text |Cite
|
Sign up to set email alerts
|

Forced swim test induces divergent global transcriptomic alterations in the hippocampus of high versus low novelty-seeker rats

Abstract: BackgroundMany neuropsychiatric disorders, including stress-related mood disorders, are complex multi-parametric syndromes. Susceptibility to stress and depression is individually different. The best animal model of individual differences that can be used to study the neurobiology of affect regards spontaneous reactions to novelty. Experimentally, when naive rats are exposed to the stress of a novel environment, they display a highly variable exploratory activity and are classified as high or low responders (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 67 publications
(87 reference statements)
1
7
0
Order By: Relevance
“…The up-regulation occurred together with the activation of anti-apoptotic protein expression. Interestingly, in addition to the midbrain raphe nuclei, the main serotonergic region of the brain [ 7 , 63 ], similar interrelation between the enzyme gene expression and cell-viability processes were found in the hippocampus [ 64 ]. In this study, using a whole transcriptome analysis, it was found that rats with low responsiveness to stress of a novel environment had increased hippocampal expression of tph2 as well as of genes related to neuroprotection at 24 h following the second forced swim exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The up-regulation occurred together with the activation of anti-apoptotic protein expression. Interestingly, in addition to the midbrain raphe nuclei, the main serotonergic region of the brain [ 7 , 63 ], similar interrelation between the enzyme gene expression and cell-viability processes were found in the hippocampus [ 64 ]. In this study, using a whole transcriptome analysis, it was found that rats with low responsiveness to stress of a novel environment had increased hippocampal expression of tph2 as well as of genes related to neuroprotection at 24 h following the second forced swim exposure.…”
Section: Discussionmentioning
confidence: 99%
“…FST is now widely used both in basic research and in pharmaceutical screens for potential antidepressant treatments due to its high predictive validity [ 12 ]. In addition, “behavioral despair” just as increased immobility and decreased swimming or climbing in FST is, by some, considered an indication of “depressive-like” symptomatology [ 13 ]. To investigate the roles of core clock genes in the rhythm of response to FST, we characterized the circadian patterns of immobility behavior in wild type, Clock Δ19 , Per1 ( Per1 Brdm1 ) and Per2 ( Per2 Brdm1 ) mutant mice at 4 h intervals.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, choosing another behavioral readout for exploring the depressive-like dimension, such as the traditional forced swim test (FST), could have unmasked differences between control and PNS animals. While on the one hand this may be true, on the other hand, the FST could have masked the molecular alterations that we found at baseline, as it is known that exposure to a session of forced swim potently activates players and circuits that are otherwise silenced under resting conditions (Reed et al, 2012;Warden et al, 2012;Pitychoutis et al, 2014).…”
Section: Discussionmentioning
confidence: 89%